2021
DOI: 10.1139/as-2020-0033
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of eutrophication in Arctic lakes

Abstract: Lakes and ponds are dominant components of Arctic landscapes and provide food and water for northern communities. In the Greiner Lake watershed, in Cambridge Bay (Nunavut, Canada), water bodies are small (84% < 5 ha) and shallow (99% <4 m). Such characteristics make them vulnerable to eutrophication as temperatures rise and nutrient concentrations from the greening landscape increase. Here, we investigated and compared 35 lakes and ponds in the Greiner watershed in August 2018 and 2019 to determine their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 59 publications
3
7
0
1
Order By: Relevance
“…The timing of these events varies noticeably between studies and agedepth models always contain an element of uncertainty; however, evidence of warmer temperatures has been previously recognized during the first millennium CE in northern Finland (Korhola et al 2000;Luoto and Nevalainen 2018) and the circumpolar Arctic more broadly (Kaufman et al 2009). The most recent increase in CHLa corroborates the growing evidence of increasingly productive northern lakes (Michelutti et al 2005;Ayala-Borda et al 2021) and is most likely related to anthropogenic warming. For the lake flora, these productive periods were likely characterized by generally improved resource availability, especially as the record provides no evidence of increases in allochthonous (shading) lake-water TOC, and increased organic substrata but possibly also changes in water chemistry, habitats and predation (Smol and Stoermer 2010).…”
Section: Woodland Lake: Biogeochemical Evidence Of Ecosystem Changes ...supporting
confidence: 73%
“…The timing of these events varies noticeably between studies and agedepth models always contain an element of uncertainty; however, evidence of warmer temperatures has been previously recognized during the first millennium CE in northern Finland (Korhola et al 2000;Luoto and Nevalainen 2018) and the circumpolar Arctic more broadly (Kaufman et al 2009). The most recent increase in CHLa corroborates the growing evidence of increasingly productive northern lakes (Michelutti et al 2005;Ayala-Borda et al 2021) and is most likely related to anthropogenic warming. For the lake flora, these productive periods were likely characterized by generally improved resource availability, especially as the record provides no evidence of increases in allochthonous (shading) lake-water TOC, and increased organic substrata but possibly also changes in water chemistry, habitats and predation (Smol and Stoermer 2010).…”
Section: Woodland Lake: Biogeochemical Evidence Of Ecosystem Changes ...supporting
confidence: 73%
“…Continuous PAR recordings under the ice of Ward Hunt Lake have shown that the PAR often reaches levels as high as 100-200 μmol m −2 s −1 in summer (Bégin, Tanabe, Kumagai, et al, 2021). The under ice Chl-a concentrations in Arctic CB lakes were also almost two times higher than values in these lakes in summer (Ayala Borda et al, 2021), further indicating the importance of winter for northern aquatic ecosystems despite the overall low light levels. IMBEAU ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…TP is a key lake health indicator since lakes are often phosphoruslimited, but excess phosphorus can result in eutrophication and suitable conditions for harmful algal bloom (HAB) events. Recently, a naturally eutrophic lake with high TP levels was reported from near the four ERA lakes sampled here (Ayala-Borda et al, 2021). The high TP load was thought to be due to the phosphorus-rich bedrock in the immediate area combined with high snow accumulation due to local lake morphology and orientation, which resulted in the increased water tracks in early spring maintaining summer phytoplankton production.…”
Section: General Microbial Diversitymentioning
confidence: 78%